The Importance of Composition in Visual Arts - Mirali Jabbarovich Makhmudov (Academia One Publishing, 2023)
this article is intended for all pedagogical artists who are creating in the field of Fine Arts. The article summarizes the importance of composition in creative works by famous artists and the processes of composition work based on the topic
Keywords: composition; sketch; Fine Arts